(untitled) (International Journal of Food and Nutritional Sciences, 2026)
Objective: The present study aimed to synthesize a novel 5-oxo imidazoline derivative of SECNIDAZOLE through chemical modification and to evaluate its physicochemical, characterization, RP-HPLC method development and validation and biological evaluation. Methods: The synthesized derivative was purified and characterized by TLC, melting point, FT-IR, 1HNMR, Mass spectrometry, and spectral analysis. Molecular docking studies were performed against the selected biological target to predict ligand-receptor interactions and binding affinity. A simple, precise, and accurate RP-HPLC method was developed for quantitative estimation of the synthesized compound and validated according to ICH Q2 R1 guidelines. The biological activity of the synthesized derivative was assessed using suitable invitro, in vivo evaluation methods. Results: Formic acid: methanol (90:10) made up the ideal mobile phase, for HPLC method development of 5-oxo-imidazoline and the λ max was detected at 254 nm. With a total run time five minutes, the retention time was found to be 3.2 minutes. With a regression coefficient of 0.999, the method showed linearity over a concentration range of 10, 20, 30, 40, 50μg/ml. The 5-oxo-imidazoline respective recognition limits (LOD and LOQ) are 1.350μg/ml and 4.100 μg/ml respectively. %RSD values were found to be